Bali–Lombok Gap: A Distinct Geo-Biologic Border of the Wallace Line - Satyana, Awang H. (Berita Sedimentologi, 2012)
The "Wallace Line", a line that divides faunal distribution, came into being in 1863 and was named after Alfred Russell Wallace, the great English naturalist travelling the "Malay archipelago‟ or the Indonesian islands from 1854-1862. The Wallace Line separates the Oriental (Asian) fauna to the west from the Australasian fauna to the east. The original Wallace Line ran between Bali and Lombok, extending northward between Borneo/Kalimantan and Sulawesi, and between the Philippines and Indonesia. The Asian animal community includes such mammals as rhinoceroses, orang-utans, tapirs, tigers, and elephants. Animals related to Australian fauna include birds such as cockatoos, birds of paradise, marsupials and cuscuses.